Lateral Surgical Approach to Lumbar Intervertebral Discs in an Ovine Model. (13th September 2012) - Oehme, David; Goldschlager, Tony; Rosenfeld, Jeffrey; Danks, Andrew; Ghosh, Peter; Gibbon, Anne; Jenkin, Graham
Abstract : The sheep is becoming increasingly used as a large animal model for preclinical spine surgery studies. Access to the ovine lumbar intervertebral discs has traditionally been via an anterior or anterolateral approach, which requires larger wound incisions and, at times, significant abdominal retraction. We present a new minimally invasive operative technique for a far-lateral approach to the ovine lumbar spine that allows for smaller incisions, excellent visualisation of intervertebral discs, and minimal abdominal retraction and is well tolerated by animals with minimal morbidity.